INTERVENÇÕES INTERDISCIPLINARES PARA PROMOÇÃO DA ALIMENTAÇÃO SAUDÁVEL ENTRE CRIANÇAS - CASTAGNOLI, JULIANA DE LARA (2022)
Healthy eating is considered a basic human right, and involves adequate nutrient intake considering cultural and social dimensions, in addition to the choice and combination of foods and the way they are prepared. Nonetheless, ensure a nutritious diet, safe, accessible and sustainable childhood is a major challenge. In general, children consume low amounts of nutritious foods such as fruits and vegetables, in addition to being a phase characterized by vulnerability to external influences. The objective of the work was to carry out interdisciplinary interventions to improve knowledge and food choices among school-age children. This study is divided into three chapters. In Chapter 1, a bibliographic review and contextualization of the study topic were elaborated. In the second Chapter, the objective was to develop cooking workshops containing products added with vegetables that are less accepted by children and to evaluate the sensory acceptability and physicochemical composition. In Chapter 3, the aim was to assess the effect of interdisciplinary educational interventions on children's attitudes, knowledge, preferences and perceptions of different nutritional labels. The participants were schoolchildren, aged between 7 and 10 years. For the first stage of the research (Chapter 2), food acceptance was evaluated in order to verify the nutritious foods less accepted by children, for use in preparations made in cooking workshops. In these workshops, five products were made: eggplant cookies, chard muffins, watercress bread, radish pancakes and chayote sfiha. All preparations showed high Acceptability Indexes (> 85%). Higher levels of lipids, calories and fiber and lower levels of ash and moisture were found in the eggplant cookie. Lower levels of carbohydrates and calories were observed in the radish pancake, while higher levels of protein and ash were observed in the chayote and chard muffin, respectively. The products with the highest carbohydrate contents were the eggplant cookie and the watercress bread, while the Swiss chard muffin had the lowest fiber content. The second stage of the research (Chapter 3) was organized into three moments: 1) Pre-Intervention: the children completed questionnaires to assess attitudes, knowledge and preferences about nutrition labeling and about the perception of healthiness of a food product, considering different types of nutrition labels; 2) Intervention: interdisciplinary educational interventions were used as a strategy to address issues related to food nutrition labeling; 3) Post-Intervention: the questionnaires used in the Pre-Intervention were reapplied to evaluate the educational process. In general, the educational intervention improved children's attitudes and viii knowledge about nutrition labeling (p < 0.05). Also, demonstrated that this public has a greater preference for labels printed on the front of the food package. The label in the form of an alert was considered the most favorable to compare the healthiness of the food product among children, while the table was the least preferred by the participants. It is concluded that the cooking workshop is an effective educational strategy to increase the acceptability of vegetables with low acceptance by school-age children. Also, interdisciplinary educational interventions on nutrition labeling are effective in improving children's attitudes, knowledge, preferences and perceptions of different nutrition labels on a food product.